2015
DOI: 10.1007/s10557-015-6592-7
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Glucagon-Like Peptide-1 Level Attenuates Angiotensin II-Induced Tissue Fibrosis by Altering AT1/AT2 Receptor Expression and Angiotensin-Converting Enzyme 2 Activity in Rat Heart

Abstract: These results demonstrate for the first time that preservation of GLP-1 using liraglutide or linagliptin is effective in inhibiting Ang II-induced cardiac fibrosis, suggesting that these drugs could be selected as an adjunctive therapy to improve clinical outcomes in the fibrosis-derived heart failure patients with or without diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 44 publications
5
59
0
Order By: Relevance
“…As described above, linagliptin ameliorated kidney fibrosis (both tubulointerstitial fibrosis and glomerulosclerosis) and albuminuria in a murine model of type 1 diabetes without altering blood glucose levels [64]. This is consistent with studies showing antifibrotic effects of linagliptin in the heart [80][81][82][83], aorta [84] and peritoneum [85] in animal models. The antifibrotic changes in the kidneys occurred together with inhibition of the endothelial-to-mesenchymal transition (EndMT) [64], which is thought to be an important source of kidney fibroblasts [86][87][88][89] that play a key role in renal fibrosis [90].…”
Section: Antifibrotic Effectssupporting
confidence: 81%
“…As described above, linagliptin ameliorated kidney fibrosis (both tubulointerstitial fibrosis and glomerulosclerosis) and albuminuria in a murine model of type 1 diabetes without altering blood glucose levels [64]. This is consistent with studies showing antifibrotic effects of linagliptin in the heart [80][81][82][83], aorta [84] and peritoneum [85] in animal models. The antifibrotic changes in the kidneys occurred together with inhibition of the endothelial-to-mesenchymal transition (EndMT) [64], which is thought to be an important source of kidney fibroblasts [86][87][88][89] that play a key role in renal fibrosis [90].…”
Section: Antifibrotic Effectssupporting
confidence: 81%
“…TRAF3IP2 also plays a role in aldosterone-induced AT1R expression [54], suggesting a critical role for TRAF3IP2 in aldosterone and AngII crosstalk. Recently, linagliptin has been shown to suppress AT1R expression and AngII-induced cardiac fibrosis [20]. It has also been shown to inhibit AngII-induced NF-κB activation and collagen synthesis in cultured cardiac fibroblasts [55].…”
Section: Discussionmentioning
confidence: 99%
“…Study shows that activation of pulmonary ACE2 enzyme by a small synthetic molecule XNT (1-[(2-dimethylamino)ethylamino]-4-(hydroxymethyl)-7-[[(4-methylphenyl)sulfonyl]oxy]-9H-xanthene-9-one) prevents pulmonary hypertension and vascular remodeling, and suggests that pulmonary ACE2 may be a novel target for the successful control of pulmonary hypertension16. In addition of some studies showed activation of GLP-1 receptor by liraglutide increases ACE2 expression and preservation of GLP-1 is associated with a reduction of angiotensin II-induced cardiac fibrosis, and reversing right ventricular hypertrophy in type 1 diabetes rats2829. We conclude that liraglutide has a great potential as an anti-pulmonary hypertension drug.…”
Section: Discussionmentioning
confidence: 99%